IMPLEMENTATION OF A STUDENT-CENTERED APPROACH IN HIGH SCHOOL DISTANCE LEARNING - Hahina, Nataliia V.; Borysenko, Valentyna V. (Educological discourse, 2015)
In the article the experience of implementing a student-centered approach into high school distance learning is summarized, current trends in the development of distance education process are analyzed, the peculiarities of applying effective distance learning technologies are considered, the conditions and ways of using the student-centered approach as a framework of distance learning in high school are substantiated, students’ rights and opportunities in the conditions of application of the student-centered approach in the process of distance learning are determined. The authors suggest practical ways of implementing student-centered learning in distance education; emphasize the key role of independent learning activities as an important aspect of distance learning, the choice of optimal approaches to the organization of educational process; prove the importance of pedagogical support and counselling to promote students’ autonomy and increase the role of self-education.